Pengembangan Intervensi Konseling Naratif Berbasis Digital dalam Menjawab Tantangan era revolusi Industri 4.0 - Amdani Sarjun; Anisa Mawarni (Indonesian Journal of Educational Counseling, 2019)
DEVELOPMENT OF NARRATIVE COUNSELING INTERVENTION OF DIGITAL-BASED IN RESPONDING TO THE CHALLENGE OF THE INDUSTRIAL REVOLUTION ERA 4.0. The Industrial Revolution 4.0 now provides changes that are fast and erratic in all aspects of life, including in the field of education, especially in the field of guidance and counseling. This condition brings opportunities as well as challenges, especially for the millennial generation and for actors who have a role in education, especially in the realm of guidance and counseling in the field in service delivery practices. Narrative counseling is a postmodern counseling approach born of ideas in a post-structuralist philosophy that is very coherent to answer conditions and situations of uncertain change. The purpose of this study is to develop and find out the development of digital-based narrative counseling in balancing changes in the all-going to the digital era, which is now a center for militaries. The method of research is using a qualitative approach to critical study methods. The results show an effective process for narrative counseling services with digitally based on every social media platform currently used by millennials.